Project Management : A Value Creation Approach - Clegg, Stewart R. (SAGE Publications, Ltd. (UK), 2020)
Project management is an essential life and workplace skill that everyone must develop. Following the popular style and format of other textbooks by Stewart Clegg, this brand new co-authored textbook on project management provides a much needed European perspective to the subject. Drawing on the latest research and practice, the authors guide students on an active learning journey through the project lifespan, promoting a critical and reflexive approach to studying project management, as well as one that creates value for all project stakeholders and emphasizes people and not just process. Case studies and examples discussed in the text cover a wide range of projects from large to smaller across different industries and sectors, both public and private, including: megaprojects (HS2); mega events (Olympics); political projects (Brexit); health-related project implementation (LEAN); tech-related projects (Google); building and restoration projects (housing/Sagrada Familia); and arts and cultural projects (European Capital of Culture). Incorporating a host of learning features both in chapters and via the supporting online resources, this textbook is essential reading for all students/managers completing a course unit in project management at either undergraduate or postgraduate level.